Perencanaan Proyek Pembangunan Office Centre Anfen Jalan Pringgading – Semarang - Andre Andre; Stefen Sambuhak; David Widanto; Widija Suseno (G-SMART, 2018)
AnFen Office Center building is used for office rentals, expected to be a place of business opportunity. The AnFen Office Center building includes office buildings that are used for professional business, administrative or commercial operations. This building has 5 floors with an area of ± 2023,44 m2. The roof of the building is planned using a concrete plate. The shear wall is planned to use the type of l frame wall from the ground floor to the 5th floor which aims to withstand the lateral force caused by the earthquake.Calculation of structures in AnFen Office Center building using SNI 03-1726-2012 for earthquake resistant building count and SNI 03-2847-2002 for construction calculation. Lower structure planning includes pile foundation, pile cap, tie beam, while the top structure includes floor plate, column, beam, roof plate, ladder and shear wall. In the calculation of moments and reactions that work on this building using software SAP 2000 Version 17.2.0.The result of design calculation of floor plate plate with thickness of 20 cm for ground floor plate and 12 cm for floor plate plate 1-5 up to roof plate. Design of beam design with dimensions B1 = 450 × 700, B2 = 300×550. Design planning column with design K1 = 800 x 800. Design planning pile foundation diameter 60 cm at a depth of 12 m.